PENGARUH KOMPETENSI APARATUR, PENERAPAN PENGANGGARAN BERBASIS KINERJA DAN PENGAWASAN FUNGSIONAL TERHADAP LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KABUPATEN ACEH UTARA - Mukhlisul Muzahid (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
This study aims to test empirically the effect of apparatus competence, performance-based budgeting and functional supervision simultaneously or partially on the performance accountability reports of government agencies in North Aceh Regency. The analytical tool used is multiple regression analysis techniques, the relationship between variables in the study is correlative and causality. Respondents in this study were heads of agencies or employees involved in the accountability report, totaling 66 respondents, because it was believed that they had broad access to the budget process. The data sources used in this study are primary and secondary data, namely through questionnaires and interviews. The results of this study indicate that simultaneously the influence of apparatus competence, performance-based budgeting and functional supervision has an effect on the performance accountability reports of government agencies, and partially the influence of competence, performance-based budgeting and functional supervision has a positive effect on the performance accountability reports of government agencies in North Aceh district. This research is expected to become a guideline and consideration for local governments, especially North Aceh district, so that apparatus competence, performance-based budgeting and functional supervision can be applied in the process of preparing government agency performance accountability reports.Keywords: Competence, Budget, Control and Performance Report.